An Optimized High-Throughput Immuno-Plaque Assay for SARS-CoV-2 - Amarilla, Alberto A.; Modhiran, Naphak; Setoh, Yin Xiang; Peng, Nias Y. G.; Sng, Julian D. J.; Liang, Benjamin; McMillan, Christopher L. D.; Freney, Morgan E.; Cheung, Stacey T. M.; Chappell, Keith J.; Khromykh, Alexander A.; Young, Paul R.; et al. (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) has been identified as the causative agent of coronavirus disease 2019 (COVID-19) and is capable of human- to- human transmission and rapid global spread. The rapid emergence and global spread of SARS-CoV-2 has encouraged the establishment of a rapid, sensitive and reliable viral detection and quantification methodology. Here, we present an alternative assay, termed immuno-plaque assay (iPA), which utilises a combination of plaque assay and immunofluorescence techniques. We have extensively optimised the conditions for SARS-CoV-2 infection and demonstrated the great flexibility of iPA detection using several antibodies and dual-probing with two distinct epitope-specific antibodies. In addition, we showed that iPA could be utilised for ultra-high throughput viral titration and neutralisation assay within 24h and is amenable to 384-well format. These advantages will significantly accelerate SARS-CoV-2 research outcomes during this pandemic period.